2022
DOI: 10.1111/vru.13067
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral vascular canal dysplasia in French and English Bulldogs: Clinical, CT, and MRI characteristics and prevalence

Abstract: The authors have observed a vertebral anomaly in French and English Bulldogs and termed this anomaly “vertebral vascular canal dysplasia (VVCD).” No previously published descriptions of this anomaly were found. The aims of this retrospective, multi‐institutional, observational study were to (1) describe the clinical, CT, and MRI characteristics of VVCD, and (2) estimate the prevalence and describe the characteristics of VVCD in a group of French and English Bulldogs. For descriptions of the anomaly, medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Computed tomography studies on the canine venous plexus in the thoracolumbar region revealed that the internal vertebral venous plexus was found to occupy the largest cross-sectional area relative to the vertebral canal cranially to the L1 vertebra ( 29 , 30 ). French bulldogs are known for their marked variation from general anatomy such as vertebral malformation or vertebral body vascular dysplasia ( 14 , 31 ). Vertebral body vascular dysplasia was not observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography studies on the canine venous plexus in the thoracolumbar region revealed that the internal vertebral venous plexus was found to occupy the largest cross-sectional area relative to the vertebral canal cranially to the L1 vertebra ( 29 , 30 ). French bulldogs are known for their marked variation from general anatomy such as vertebral malformation or vertebral body vascular dysplasia ( 14 , 31 ). Vertebral body vascular dysplasia was not observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially a specific phenotype predisposes the pug for both these debilitating conditions and that breed-related characteristics cause health problems not previously associated with the brachycephalic syndrome ). It has recently been suggested that a broader definition, or term, of 'the brachycephalic syndrome' is warranted to incorporate the prevalence of all reported vertebral and cranial abnormalities in these types of breeds (Santifort et al 2022).…”
Section: Associated Conditions Of Abnormal Gaitmentioning
confidence: 99%
“…However, anomalies exist, and the spinal cord or vertebral column of an individual patient can differ from what is described in textbooks. Abnormally shaped vertebrae such as hemivertebrae, butterfly-shaped vertebrae, and, more recently, vertebral vascular canal dysplasia, or spinal malformations such as spinal dysraphism or arachnoid diverticula, are frequently diagnosed [3][4][5].…”
Section: Introductionmentioning
confidence: 99%